Delayed blastulation and pregnancy outcomes in single frozen-thawed euploid blastocyst transfer - Lang, Jingwen; Hong, Ling; Yang, Wanli; Wang, Qiaoling; Zhi, Yunqing; Zhu, Xiuxian; Fu, Yonglun (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to evaluate the impact of embryo developmental speed on clinical outcomes in euploid blastocyst transfers, with a focus on maternal age and embryo morphological quality.MethodsA retrospective cohort study was conducted, including patients who underwent single blastocyst transfer following preimplantation genetic testing. Embryos were categorized based on developmental speed (day 5 vs. day 6 blastocysts) and further stratified by maternal age and embryo morphological quality. Clinical outcomes were compared between groups.ResultsDay 5 euploid blastocysts yielded significantly higher implantation (68.8% vs. 48.3%) and live birth rates (63.7% vs. 40.4%) than day 6 blastocysts. In the advanced-age group, day 5 euploid embryos demonstrated significantly higher implantation (72.5% vs. 40.5%) and live birth rates (68.8% vs. 28.6%) than day 6 embryos. Developmental speed influenced pregnancy outcomes in low-quality embryos, where day 6 blastocysts exhibited a reduced live birth rate (29.3% vs. 65.5%) than day 5 blastocysts.ConclusionOur findings indicate that day 5 euploid embryos are associated with better pregnancy outcomes compared to day 6 euploid embryos, with this trend being more pronounced in older participants and lower-quality embryo groups. However, day 6 euploid blastocyst transfer also yields acceptable implantation and pregnancy outcomes.